The psychological factors related to the usage of electronic devices among adolescents in Macau - Chan, Ka Pou (University of Saint Joseph, 2018)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Family Support, Job Insecurity, Coronavirus Stress and Leadership Styles Effects on Burnout and Work Engagement in Hospitality during Covid-19 Pandemic in Macau - Chang, Pou I. (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Organisational Psychology (MOP); University of Saint Joseph

The Impacts of Burnout and Work Engagement on Performance: a Study of a Surveillance Team - Chang, Pou I. (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

The Indirect Effect of Job Insecurity and COVID-19 Induced Stress on Mental Health through the Mediating Effect of Burnouts and the Moderating Effect of Perceived Social Support among Macau Gaming Employees - Hoi, Lok (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Primary teachers' burnout at the inclusive education schools in Macao - Ieong, Iek Kuan (University of Saint Joseph, 2023)
"In 2021/2022 academic year, there are 2,244 SEN students in Macau and its growth rate is 36% in ten years. However, at the present, there are 38 schools providing the related education to them. Admittedly, this is an unbalanced supply and demand. In fact, the teachers who work at inclusive education schools are bearing all responsibility to teach SEN students and their mental health is worth to attention. Moreover, there are 1,224 SEN students in primary (2021/2022 academic year), it accounting for 55% of all. That is, the numbers of their teachers are the most and they are representative. Therefore, exploring primary teachers’ burnout at inclusive education schools becomes the topic of this study, even more important, it is including to compare normal and resource teachers. This topic is rarer currently in Macau. On the one hand, emotional exhaustion, depersonalization and (reduced) personal accomplishment are dimensions of burnout (Maslach et al., 1996). These become the dependent variables of this study. According Ecological Systems Theory (Bronfenbrenner, 1979) and the factors of self-efficacy in inclusive education (Sharma et al., 2012), the following hypotheses are provided to guide this study: (1) normal teachers’ emotional exhaustion, depersonalization and reduced personal accomplishment are higher than those in resource teachers; (2) teachers’ attitudes into inclusive education, (3) teachers’ self-efficacy to use inclusive instruction (SEII), (4) teachers’ self-efficacy in collaboration (SEC) and (5) teachers’ self-efficacy in v managing behavior (SEMB) both are negatively related to emotional exhaustion, depersonalization and reduced personal accomplishment; (6) teachers’ stress of Covid19 is positively related to emotional exhaustion, depersonalization and reduced personal accomplishment. On the other hand, quantitative methodology, and snowball sampling are used in this research. At last, 132 responds are collected, including 100 normal teachers and 32 resource teachers. They are from 48 inclusive education schools in Macau. All data were analyzed by SPSS 25.0. The results of this study are followed: (1) teachers’ emotional exhaustion level is middle, their depersonalization and reduced personal accomplishment levels both are low; (2) resource teachers’ emotional exhaustion and depersonalization are higher than normal teachers; (3) teachers’ attitudes into inclusive education negatively related to depersonalization but positively related to reduced personal accomplishment; (4) in the factors of self-efficacy, only SEII is negatively related to reduced personal accomplishment; (5) teachers’ stress of Covid-19 is positively related to emotional exhaustion, depersonalization and reduced personal accomplishment."
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

The Effect of Peers, School Connectedness, Parents on Internet Gaming Addiction in Adolescents - Ip, Tan Long (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Conceptions of giftedness in Macau - Leong, Nga Ut (University of Saint Joseph, 2018)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Effects of parenting styles, parent expectations, and academic results on Macau adolescent's self-esteem - Mak, Chi Kwan (University of Saint Joseph, 2018)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Can The Organisation Help? Exploring The Relationship Between Emotional Intelligence, Resilience And Burnout Among Counselling Professionals With Organisational Socialisation As Moderator - Mak, Sin Kei (University of Saint Joseph, 2023)
The phenomenon of burnout has been recognised as a worldwide occupational health issue after being vastly studied for decades. Trait Emotional Intelligence (trait EI) and resilience have been identified as personal protective factors (Gutierrez & Mullen, 2016; Listopad et al., 2021), while organisational socialisation is suggested to be an organisational factor in helping people in preventing burnout (Taormina & Law, 2000). With the purpose of 1) investigating the phenomenon in the counselling profession, as well as 2) exploring how trait EI and resilience are related to burnout and whether organisational socialisation might impose moderating effects in between, the present study examined 115 counselling professionals currently employed and working in organisational settings in Macau by snowball sampling, using a quantitative and cross-sectional approach through self-reported online questionnaires. From the data obtained, different burnout patterns were observed according to job titles and work settings, indicating that counselling professionals with different specialties and work in different settings have unique sources of stress, which resulting in differences in their burnout patterns. No between-group differences were observed in age and work experience, while male participants have a higher burnout perception than female participants in the current study. On the other hand, current results suggested trait EI and four components of resilience (determination, endurance, adaptability and recuperability) are negatively correlated to counselling professionals’ burnout perception, providing supportive evidence that trait EI and resilience are protective factors against burnout. Moderation analysis results revealed that organisational socialisation has some moderating effects on the relationship between trait EI, resilience and burnout. However, differences in direction and intensity indicated that the moderating effects of organisational socialisation might be influenced by individual differences. Further studies are needed to better the understanding of the moderating effect of organisational socialisation. Limitations of the current research and implications for counselling professionals and organisations were also discussed in the study
Keywords: Thesis and Dissertations Master of Organisational Psychology (MOP); University of Saint Joseph; burnout; counselling professionals; organisational socialisation

Attitudes towards counseling between iran and Macau universities students - Rashinia, Jafar (University of Saint Joseph, 2016)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Emotional Support Influence Work Engagement and Mental Well-being in Macau: The Moderating Effect of Self-reflection - Sou, Kam Chan; Kuok, Angus C. H. (University of Saint Joseph, 2023)
The purpose of this study is to examine work engagement and mental well-being in Macau, specifically after more than three years of COVID. Examine whether external factors such as emotional support from supervisors, co-workers, and family members have a positive impact on work engagement and mental well-being, and whether the internal factor self-reflection with its three aspects of need for self-reflection, engagement in self-reflection, and insight from self-reflection moderates the relationship between emotional support, work engagement, and mental well-being. The target audience consists of Macau's integrated resort, hospitality, and gaming industry employees. According to the Affective Event Theory (AET), affective events at work generate emotional responses that influence the attitudes and behavior of employees in the workplace. In this study, this theoretical framework was used to clarify the interplay of variables that explain emotional support from supervisors, co-workers, and family members, work engagement, and mental well-being. An online self-response survey (N=325) was used to conduct quantitative and cross-sectional research. There was also a combination of simple random sampling, convenience sampling, and referral sampling. All variables were found to be correlated, and while perceived supervisor support was a significant predictor of all aspects of work engagement and mental well-being, family and co-worker support only predicted certain aspects of these variables. Self-reflection partially moderated the positive effects of certain emotional support on work engagement and mental well-being
Keywords: Co-worker Support; Emotional Support; Family Support; Mental Well-being; Perceived Supervisor Support; Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph; Work Engagement

THE EFFECTS OF TEACHER SELF-EFFICACY AND PERCEIVED AUTONOMY ON TEACHER WORK ENGAGEMENT: THE MEDIATING EFFECT OF PERCEIVED ORGANISATIONAL SUPPORT - Wan, Sok Leng (University of Saint Joseph, 2023)
The aims of the present study are to investigate the level of work engagement of the inclusive teachers in Macau and what potential factors would contribute to the increase of their level of work engagement. In this research, the framework of the self-determination theory developed by Ryan and Deci in 2000 was partially employed. I suggested the inclusive teachers’ self-efficacy and perceived autonomy to act as the independent variables, while perceived organisational support was involved as the mediating variable. Quantitative method was applied in this study by using an online self-response questionnaire (N= 150). The stratified sampling strategy was applied as well in order to ensure the representativeness. No gender difference of work engagement level was found among Macau inclusive teachers. Positive correlations were found among all variables. Besides, perceived organisational support was expressing positive mediating effects on the relationships between independent and dependent variables under some specific circumstances. For example, the relationship between efficacy to use inclusive instructions and emotional and physical work engagement; the relationship between perceived autonomy and cognitive, emotional, and physical work engagement. Theoretical and practical implications for the non-tertiary schools and inclusive teachers can be found in this study. Future studies should be continued to investigate the limitations and suggestions of this field of research
Keywords: PERCEIVED ORGANISATIONAL SUPPORT; TEACHER PERCEIVED AUTONOMY; TEACHER SELF-EFFICACY; Thesis and Dissertations Master of Organisational Psychology (MOP); University of Saint Joseph; WORK ENGAGEMENT

The Effects of Family Support, Friends Support, Supervisor Support, Co-worker Support, and Organizational Support to Resilience and its Effects to Work Engagement - Wong, Sio Peng (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Organisational Psychology (MOP); University of Saint Joseph

The Effect of Organizational Justice on Work Engagement Between Foreigner and Local Workers in Macau: The Moderating Effect of Organizational Commitment - Wong, Wai Fai (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Organisational Psychology (MOP); University of Saint Joseph